Aufgeklebte Zeitungsartikel und Ausstellungsflyer (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Painting; Newspapers; Art historians; Painters; Archives; Exhibitions; Art Exhibition; Newspaper Article; Flyer